2003
DOI: 10.1590/s1415-47572003000400015
|View full text |Cite
|
Sign up to set email alerts
|

A homolog of the RPS2 disease resistance gene is constitutively expressed in Brassica oleracea

Abstract: In this study, we identified disease resistance gene homologs in Brassica oleracea and assessed their expression in lines resistant and susceptible to Xanthomonas campestris pv. campestris (Xcc). Two DNA fragments of approximately 2.5 kb (BI-16/RPS2 and Lc201/RPS2) were amplified by PCR from two Brassica lines using primers based on an RPS2 homologous sequence previously described in the Brassica oleracea ecotype B117. The sequences of these fragments shared high similarity (95-98%) with RPS2 homologs from var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Earlier Wroblewski et al [ 50 ] identified RPS2 homologs with high nucleotide similarity in Brassica species, like B. montana AF180358 (98% identity), B. oleracea AF180357 (98% identity) and B. rapa AF180359 (95% identity). Later Malvas et al [ 51 ] also described the involvement of B. oleracea RPS2 homolog in disease resistance which is constitutively expressed. In our study, two CNL type NBS genes, one in B. rapa (Bra013947-previous GenBank ID AF180359) and one in B. oleracea (Bol039594- previous GenBank ID AF180357) were found to be conserved parallel to the RPS2 gene with 94.59% nucleotide similarity.…”
Section: Resultsmentioning
confidence: 99%
“…Earlier Wroblewski et al [ 50 ] identified RPS2 homologs with high nucleotide similarity in Brassica species, like B. montana AF180358 (98% identity), B. oleracea AF180357 (98% identity) and B. rapa AF180359 (95% identity). Later Malvas et al [ 51 ] also described the involvement of B. oleracea RPS2 homolog in disease resistance which is constitutively expressed. In our study, two CNL type NBS genes, one in B. rapa (Bra013947-previous GenBank ID AF180359) and one in B. oleracea (Bol039594- previous GenBank ID AF180357) were found to be conserved parallel to the RPS2 gene with 94.59% nucleotide similarity.…”
Section: Resultsmentioning
confidence: 99%
“…Malvas et al . (2003) identified two DNA fragments of RPS2 gene homologues in two Brassica lines resistant and susceptible to Xcc. The digestion of these fragments with restriction enzymes showed polymorphisms at the XbaI restriction sites.…”
Section: Restricted Fragment Length Polymorphismmentioning
confidence: 99%
“…RFLP markers have been used in studying genetic variability and relationships in plant species, for example, Lathyrus (Chtourou-Ghorbel et al, 2001) and Pleurotus eryngii (Urbanelli et al, 2007). RFLP markers have also been used in assessing genetic variation and developing detailed genetic maps of Brassica (Diers and Osborn, 1994;Diers et al, 1996;Pradhan et al, 2003) and lettuce (Landry et al, 1987;Kesseli et al, 1994), assessing polymorphisms in Brassica lines resistant and susceptible to Xcc (Malvas et al, 2003;El-Esawi, 2012), and identification of origin of cultivated lettuce (Kesseli et al, 1991). Malvas et al (2003) identified two DNA fragments of RPS2 gene homologues in two Brassica lines resistant and susceptible to Xcc.…”
Section: Restricted Fragment Length Polymorphismmentioning
confidence: 99%